2019
DOI: 10.1109/tbme.2018.2821201
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ultrasonic Neuromodulation in Freely Moving Mice

Abstract: Neuromodulation is a fundamental method for obtaining basic information about neuronal circuits for use in treatments for neurological and psychiatric disorders. Ultrasound stimulation has become a promising approach for noninvasively inducing neuromodulation in animals and humans. However, the previous investigations were subject to substantial limitations, due to most of them involving anesthetized and fixed small-animal models. Studies of awake and freely moving animals are needed, but the currently used ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…However, even for the larger animal, head-fixation was still required for the experiment. There exists only one study which reported neuromodulation of local field potential (LFP) using a miniature single-element transducer [16]. Since the same stimulation modality is preferred to translate the findings from pre-clinical to clinical trials, to observe…”
Section: Introductionmentioning
confidence: 99%
“…However, even for the larger animal, head-fixation was still required for the experiment. There exists only one study which reported neuromodulation of local field potential (LFP) using a miniature single-element transducer [16]. Since the same stimulation modality is preferred to translate the findings from pre-clinical to clinical trials, to observe…”
Section: Introductionmentioning
confidence: 99%
“…Electric impedance can be matched with simple shunt and series inductors to cancel the reactive component of the transducer [107][108][109]. Optimization of the EIMNs with driver/receiver electronics for broadband application in high-frequency range is difficult.…”
Section: Methods Of Electrical Impedance Matchingmentioning
confidence: 99%
“…Most of the previous works demonstrated ultrasound neuromodulation on immobile or sedated animals because commercially available transducers are often bulky, heavy, and requires a collimator [19][20][21][22][23][24][25]. Recently, three pioneering works on MEMS-based ultrasound transducers have successfully demonstrated in vivo neuromodulation in freely-moving behaving animals [38][39][40][41]. The first of these reports was based on a CMUT ring array composed of 32 elements with a 183-kHz resonant frequency [38,39].…”
Section: In Vivo Neurotoolsmentioning
confidence: 99%
“…The other two works were based on piezoelectric transducers (Table 1) [40,41]. Lee et al [41] developed a miniaturized tFUS system for freely-moving animals.…”
Section: In Vivo Neurotoolsmentioning
confidence: 99%
See 1 more Smart Citation